Photoelastic analysis of stress generated by wires when conventional and self-ligating brackets are used: A pilot study - Guilherme Caiado Sobral; Mário Vedovello Filho; Viviane Veroni Degan; Milton Santamaria Jr (Dental Press Editora, 2014)
OBJECTIVE: By means of a photoelastic model, this study analyzed the stress caused on conventional and self-ligating brackets with expanded arch wires. METHOD: Standard brackets were adhered to artificial teeth and a photoelastic model was prepared using the Interlandi 19/12 diagram as base. Successive activations were made with 0.014-in and 0.018-in rounded cross section Nickel-Titanium wires (NiTi) and 0.019 x 0.025-in rectangular stainless steel wires all of which made on 22/14 Interlandi diagram. The model was observed on a plane polariscope - in a dark field microscope configuration - and photographed at each exchange of wire. Then, they were replaced by self-ligating brackets and the process was repeated. Analysis was qualitative and observed stress location and pattern on both models analyzed. CONCLUSIONS: Results identified greater stress on the region of the apex of premolars in both analyzed models. Upon comparing the stress between models, a greater amount of stress was found in the model with conventional brackets in all of its wires. Therefore, the present pilot study revealed that alignment of wires in self-ligating brackets produced lower stress in periodontal tissues in expansive mechanics.